REVITALIZING NATIONAL POLITICAL VALUES THROUGH THE SOCIO-POLITICAL MOVEMENTS OF THE TAREKAT: Studied at the political social role of tarekat Qadiriyah wa Naqsyabandiyah in Nusantara - Amir Maliki Abitolkha; Muhamad Basyrul Muvid; Maulana Arafat Lubis (IAIN Ponorogo, 2020)
Abstract:The tarekat is not only understood as a spiritual-religious organization, but also a socio-political organization capable of contributing to the nation's sovereignty and independence. This research aims to find and analyze the process of revitalizing the national political values of the QadiriyahwaNaqsyabandiyah order. The method used is studying literature by digging into various references, documentation, and journals that correspond to the topic. From the literature, it was found that the QadiriyahwaNaqsyabandiyahtarekat successfully played its socio-political role to help the People and People of Indonesia get out of the difficulties, sufferings, and tribulations of colonialism. Because its role as social jam'iyah is minimal, so tarekat extends to the religio-political aspect. Then, the process of revitalizing the national political values of the Qadiriyah wa Naqsyabandiyah order can be seen from several steps: through the role of the elite of the order, through the religio-political system, relations with political parties, through the synergy between the encouragement of Islamic teachings, the motivation of individuals and groups, and interaction with the outside world, through the function of the order as a religious and social institution. الملخص :ولا يُفهم الأمر على أنه منظمة دينية روحية فحسب، بل هو منظمة اجتماعية وسياسية قادرة على المساهمة في سيادة الأمة واستقلالها. والغرض من هذا البحث هو إيجاد وتحليل عملية تنشيط القيم السياسية الوطنية للرهبانية القادرية والنقشبندية. الطريقة المستخدمة هي دراسة الأدب من خلال البحث في مراجع ووثائق ومجلات مختلفة تتوافق مع الموضوع. وكانت النتيجة أن قامت رهبانية القادرية والنقشبندية بنجاح بدورها الاجتماعي - السياسي لمساعدة شعب وشعب إندونيسيا على الخروج من الصعوبات والمعاناة والمحن التي يعاني منها الاستعمار. دور الجامية الاجتماعية الدينية محدود جداً، لذلك يمتد إلى الجانب التديني والسياسي. ثم يمكن رؤية عملية تنشيط القيم السياسية الوطنية للرهبانية القادرية والنقشبندية من عدة خطوات: من خلال دور نخبة النظام، من خلال النظام التديني - السياسي، والعلاقات مع الأحزاب السياسية، من خلال التآزر بين تشجيع التعاليم الإسلامية، ودوافع الأفراد والجماعات، والتفاعل مع العالم الخارجي، من خلال وظيفة النظام كمؤسسة دينية واجتماعية.Abstrak:Tarekat tidak hanya dipahami sebagai organisasi keagamaan spiritual, semata, namunia sebagai organisasi social politik yang mampu memberikan kontribusi terhadap kedaulatan dan kemerdekaan bangsa. Tujuan penelitian ini ingin menemukan dan menganalisis proses revitalisasi nilai-nilai politik kebangsaan tarekat Qadiriyah wa Naqsyabandiyah. Metode yang digunakan adalah studi kepustakaan dengan menggali berbagai referensi, dokumentasi, dan jurnal-jurnal yang sesuai dengan topik. Hasil yang ditemukan ialah Tarekat Qadiriyah wa Naqsyabandiyah berhasil memainkan peran sosial politiknya untuk membantu masyarakat dan bangsa Indonesia keluar dari kesulitan, penderitaan dan kesengsaraan akibat penjajahan. Peran sebagai jam’iyah social keagamaan sangat terbatas, sehingga diperluas kepada aspek religio-politik. Kemudian, proses revitalisasi nilai-nilai politik kebangsaan tarekat Qadiriyah wa Naqsyabandiyah dapat dilihat dari beberapa langkah: melalui peranan elit tarekat, melalui system religio-politik, relasi dengan partai politik, melalui sinergitas antara dorongan ajaran Islam, motivasi individu dan kelompok, dan interaksi dengan dunia luar, melalui fungsi tarekat sebagai lembaga keagamaan dan sosial.